HUBUNGAN KECERDASAN EMOSIONAL TERHADAP PERILAKU MORAL SISWA KELAS X TKJ SMK MUHAMMADIYAH DI KOTA PEKANBARU - Nurmaulista YM; vitriani; Finanta (Unit Pelaksana Praktik Kependidikan Terpadu Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Riau, 2023)
This thesis discusses the low emotional intelligence of students. Emotional intelligence is a person's ability to recognize, manage emotions, motivate himself, empathize, and have good interpersonal relationships with others. The low emotional intelligence of students is due to the fact that there are still students who make turmoil in the classroom, students who fight, students that speak rude, and friends who insult each other. The study aims to determine the level of emotional intelligence related to the moral behavior of SMK Muhammadiyah students in Pekanbaru City. As for the sample in this study, there were 153 students. The method used in this study is quantitative correlation to look at the relationship between emotional intelligence and moral behavior. Data analysis techniques using Pearson Product Moment correlation testing with the help of IBM SPSS for Windows Ver.26. The results of the hypothesis test obtained the value of the correlation coefficient rxy = 0.603 and the determinant factor value resulted in 36.3%. Based on the result of the test of the hypothetics received there is a significant positive relationship between emotional intelligence to the moral behavior of students of class X TKJ SMK Muhammadiyah in Pekanbaru City which means that emotional Intelligence has an influence of 36.3% on moral behaviour.